Galois groups and fundamental groups - Szamuely, Tamás (Cambridge studies in advanced mathematics, 2009)
This book presents the connection between Galois groups in algebra and fundamental groups in topology. Starting at an elementary level, it shows how the judicious use of algebraic geometry gives access to the powerful interplay between algebra and topology that underpins much modern research in geometry and number theory.